Comparing the lifestyles of first and final term female BS nursing students - Baroogh; N. Nuktehdan; H. Kazemnejad; A. Nuruzi; E (Tehran University of Medical Sciences, 2003)
Consideration of the lifestyles of nursing students, because of the fact that they are at the age where their choice of lifestyle can influence their entire lives, is of vital importance. On the other hand nursing students are conveyors of health information and are responsible for guiding others towards the way of life therefore they themselves need to be appropriate models for those in need of help and the society as a whole. This study is a descriptive research, whose aim is comparing the lifestyle of first and final term female BS nursing students. This investigation was undertaken in Nursing and Midwifery schools of Tehran Medical Science Universities, by sampling 139 students in their first term and 159 students in their final term. The factors of life style under examination were nutrition, exercise, smoking, safety precautions and stress management. The method of data collection was questionnaires that consisted of demographic and life style particularities. Research findings showed that 37.4% of the first term students had moderate nutrition and 49.9% had good nutrition. As concerns physical exercise (37.4%) and (41.1%) of the first and final term students had moderate physical exercise respectively. Research findings also showed that none of the students of either two groups smoked cigarettes. As relates to safety precautions results showed that 37.2% first term students and 35% in final terms students had moderate behavior. In stress management (36.5%) first term students and (32.9) last term students had good behavior. In general (40%) of the samples in their first term had moderate lifestyles while (32.8%) in their last term had very good lifestyles. "t" Statistical test showed no significant difference between the two groups. Research findings showed that nursing education and training in no way influenced life style and that other factors were influential but they require further study.